Dysregulation of Hnf1b Gene Expression in Cultured Beta-Cells in Response to Cytotoxic Fatty Acid - Johnstone, Karen A; Diakogiannaki, Eleftheria; Dhayal, Shalinee; Morgan, Noel G; Harries, Lorna W (JOP. Journal of the Pancreas, 2011)
Context Increased levels of circulating fatty acids deriving from over-nutrition are thought to contribute to the progressive beta-cell failure associated with type 2 diabetes. Pancreatic beta-cells in culture are sensitive to exposure to long-chain saturated fatty acids (e.g. palmitate) which cause cytotoxicity, whereas the monounsaturated equivalents (e.g. palmitoleate) are cytoprotective. Objectives In this study we sought to determine whether of members of the hepatocyte nuclear factor (HNF) family of transcription factors, which are mutated in familial, young-onset, monogenic beta-cell diabetes, could play a role in fatty acid-mediated cytotoxicity in cultured beta-cells. Design We used real-time PCR to determine whether hepatocyte nuclear factor gene expression was altered in response to palmitate exposure in the BRIN-BD11 beta-cell line. Results We found that the Hnf isoforms expressed in BRIN-BD11 cells are dysregulated by palmitate exposure. The expression of Hnf1b is specifically reduced by exposure to palmitate, and this response is prevented by co-incubation with palmitoleate. Conclusions Down-regulation of Hnf1b gene expression accompanies palmitate-mediated cytotoxicity in cultured beta-cells. Image: Hnf1b expression is downregulated in response to cytotoxic fatty acid.